Analysis Food Security of Cities in Bengkulu Province Pre and Post Pandemic - Wibowo, Hariz Eko; Novanda, Ridha Rizki; Ifebri, Rihan; Fauzi, Ariffatchur (AGRITROPICA : Journal of Agricultural Sciences, 2024)
The percentage of the population living in poverty in Bengkulu Province was not affected by the pandemic and even tended to decrease. This is contrary to the findings of studies on the impact of the pandemic on income, poverty, and food security. One way to determine the impact of the pandemic on food security is by comparing the conditions before and after the pandemic. Based on the descriptive analysis results, the food Security Index in some districts increased steadily throughout the period, but others fluctuated. Some districts experiencing fluctuations include Rejang Lebong, Seluma, and Mukomuko. The Food Security Index of other districts, including Bengkulu City, tends to increase. Only the Food Security Index of Kepahiang and Bengkulu Tengah districts shows a tendency to decrease. The results of the paired sample t-test indicate a significant difference in the food security index among districts and cities in Bengkulu Province between before and after the pandemic. This finding aligns with the descriptive analysis results that show a difference in the food security index among districts and cities in Bengkulu Province. Further analysis was conducted by considering these three aspects. However, the three aspects yielded different results in the paired sample t-test. Only in terms of food quality, the paired sample t-test results showed a significant difference in quality index between before and after the pandemic, supported by a p-value of (0.032) < alpha 5%.